Flavor Frozen Food (3F) / Raja Azrin Raja Azman ... [et al.] - Raja Azman, Raja Azrin; Mohamed, Ummi Edura; Ismail, Mohd Aminurashid; Mohamed Hussain, Siti Azura; Amiruddin, Mohamed Akmal (Faculty of Hotel and Tourism Management, 2005)
Flavour Frozen Food or 3F is a company that emphasis on selling frozen food whether to the wholesaler or straight to the customer. Located at Lot.32 Jalan Kristal 1, Seksyen 7, 40 450 Shah Alam, Selangor. 1st January 2006 is the date of the business commencement for this company.